2013
DOI: 10.1136/gutjnl-2012-303965
|View full text |Cite
|
Sign up to set email alerts
|

Narrow band imaging to differentiate neoplastic and non-neoplastic colorectal polyps in real time: a meta-analysis of diagnostic operating characteristics

Abstract: PurposeMany studies have reported on the use of narrow band imaging (NBI) colonoscopy to differentiate neoplastic from non-neoplastic colorectal polyps. It has potential to replace pathological diagnosis of diminutive polyps. We aimed to perform a systematic review and meta-analysis on the real-time diagnostic operating characteristics of NBI colonoscopy.MethodsWe searched PubMed, SCOPUS and Cochrane databases and abstracts. We used a two-level bivariate meta-analysis following a random effects model to summar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 82 publications
3
108
0
3
Order By: Relevance
“…However, the requirement for a post-polypectomy histological assessment leads to a substantial exploitation of medical and economic resources (32). In recent years, a 'resect and discard' strategy based on the findings of image-enhanced endoscopy (e.g., high-definition endoscopy, magnifying endoscopy and chromoendoscopy) for diminutive colorectal polyps has been proposed to save both the time and cost of histopathology (33)(34)(35)(36). However, there are several barriers to applying this strategy in the clinical practice of the present authors.…”
Section: Patient Age ------------------------------------------------mentioning
confidence: 99%
“…However, the requirement for a post-polypectomy histological assessment leads to a substantial exploitation of medical and economic resources (32). In recent years, a 'resect and discard' strategy based on the findings of image-enhanced endoscopy (e.g., high-definition endoscopy, magnifying endoscopy and chromoendoscopy) for diminutive colorectal polyps has been proposed to save both the time and cost of histopathology (33)(34)(35)(36). However, there are several barriers to applying this strategy in the clinical practice of the present authors.…”
Section: Patient Age ------------------------------------------------mentioning
confidence: 99%
“…A meta-analysis of 28 studies including 6280 polyps, conducted in 2013, revealed an overall sensitivity of 91% and a specificity of 82%. The concordance of the endoscopic surveillance interval based on real-time prediction, correlated with the pathological assessment, is 92,6% [6].…”
Section: Discussionmentioning
confidence: 94%
“…41 Previously published meta-analyses of VCE for optical diagnosis of colorectal polyps have also used a bivariate model to estimate pooled sensitivity and specificity. [42][43][44] We conducted separate meta-analyses for the each of the three VCE technologies relevant to this report compared with histopathology. For each technology we produced individual meta-analyses according to the level of confidence with which the polyp characterisation had been made by the endoscopist in accordance with how the data were reported in the primary studies (high-confidence predictions; all predictions irrespective of confidence level).…”
Section: Methods Of Data Synthesismentioning
confidence: 99%
“…[42][43][44]149 For example, the ASGE Technology Committee conducted a systematic review to examine whether NBI, i-scan or FICE met the PIVI performance thresholds and, therefore, whether or not the evidence supported a 'diagnosis-and-leave' approach (ASGE Technology Committee, 2015, p. 1). 149 Literature searches were done on a number of standard health research databases, up to May 2014 (thus the search is around 2 years older than our literature search).…”
Section: Doi: 103310/hta21790 Health Technology Assessment 2017 Volmentioning
confidence: 99%